Indian Agricultural Marketing- A Review - Rehman, Shakeel-Ul-; Selvaraj, M; Ibrahim , M Syed (Asian Journal of Agriculture and Rural Development, 2012)
Agriculture in India has directly or indirectly continued to be the source of livelihood to majority of the population. Indian agriculture has seen a lot of changes in its structure. India, predominantly an agricultural economy, has healthy signs of transformation in agriculture and allied activities. India has seen agriculture as a precious tool of economic development as other sectors of production depend on it. Efficient backward and forward integration with agriculture has led to globally competitive production system in terms of cost and quality. Cooperatives seem to be well positioned to coordinate product differentiation at the farm level and to integrate forward into value added processing activities.. Indian agriculture can be balanced and made efficient through proper and better management practices. The present study brings out past and present scenario of agricultural marketing prevailing in India, its challenges and future recommendations. Moreover the opportunities provide by agricultural marketing should be tapped effectively by the marketers.